SURGICAL OUTCOMES AFTER INVERTED INTERNAL LIMITING MEMBRANE FLAP VERSUS CONVENTIONAL PEELING FOR VERY LARGE MACULAR HOLES. Issue 8 (August 2019) - Narayanan, Raja; Singh, Sumit R.; Taylor, Stanford; Berrocal, Maria H.; Chhablani, Jay; Tyagi, Mudit; Ohno-Matsui, Kyoko; Pappuru, Rajeev R.; Apte, Rajendra S.
Abstract : Purpose: To evaluate the anatomical and visual outcomes of inverted flap technique of peeling of internal limiting membrane (ILM) versus standard peeling of ILM for macular holes of basal diameter more than 800 μ m. Methods: Patients with very large idiopathic macular holes more than 800 μ m in basal diameter (ranging from 243 μ m to 840 μ m in minimum diameter) were retrospectively included in the study. In Group A, 18 eyes of 18 patients underwent ILM peeling using the inverted flap technique. In Group B, 18 eyes of 18 patients underwent conventional ILM peeling. The primary endpoint was the rate of hole closure at 6 months after surgery. The secondary outcome measure was the change in best-corrected visual acuity at 6 months after surgery. Results: There were no significant differences in ocular characteristics of the study groups at baseline except for the age distribution. Mean macular hole diameter was 1, 162.8 ± 206.0 μ m and 1, 229.6 ± 228.1 μ m in Group A and Group B, respectively. The hole closure rate was 88.9% (16/18) in Group A and 77.8% (14/18) in Group B ( P = 0.66). The mean gain in best-corrected visual acuity was higher in Group A than in Group B ( P = 0.12) at 6 months, but this was not statistically significant. There were no severe ocular adverse events in either group. Conclusion: In this multicenter series, inverted ILM flap technique did not lead to significantly higher anatomical closure rates than conventional ILM peeling in large macular holes more than 800 μ m in diameter. Abstract : The inverted internal limiting membrane flap is a recent surgical technique that provides marginally better functional and anatomical results in very large macular holes compared with the conventional technique.